Computed Tomography of the Chest: Basic Principles - Sarkar, Probir Kumar; Alam, Md Jahangir (Dhaka Shishu (Children) Hospital Journal, 2021)
Tomography is a process by which an image layer of the body is produced, while the images of the structures above and below that layer are made invisible by blurring. computed tomography (CT), the most widely used cross-sectional imaging methods used in medicine, forms cross-sectional images by avoiding super-imposition of structures that occurs in conventional chest imaging, with a >10-fold increase in attenuation sensitivity, within a second without need for breath holding. Like X-ray, an imaging contrast is generated as a consequence of differences in attenuation between the adjacent tissues. The higher the attenuation of the X-ray beam, the brighter the tissue on CT images, and vice versa. The only drawback is the potentially harmful radiation that is measured according to the amount of radiation received by the whole body. Simply, the amount of radiation from a chest CT is equivalent to 400 X-rays. Standard CT usually takes the image of the whole lung and compresses thick slices of about 7-10 mm into images and contrast can be given to highlight structures. High resolution (HRCT) has excellent spatial resolution and very useful for assessing the architecture of the lung. It does not involve IV contrast, acquires thin, non-contiguous slices, at 10-15 mm intervals with thin slices of lung tissues at regular intervals. This reduces the radiation dose by up to 90% compared to standard CT. The axial images are most commonly viewed using lung, mediastinal and bone window. The pulmonary window is specially used for the interpretation of lung parenchyma, airways and interstitial tissues but the mediastinal window is for the interpretation of mediastinal structures. CT interpretation needs a structured and logical approach. DS (Child) H J 2019; 35(1) : 63-69